Cultural heritage of Central Asian Turks in written sources of the XIX century - Alzhanova, E.E.; CHETIN, Nur (KSU publ., 2020)
This article analyzes the sources related to the cultural heritage of Central Asian Turks mainly from the 19th century. The main sources were collected and studied at the National Library of Uzbekistan, which is themost complete collection of materials on the cultural and historical heritage of Central Asian Turks. The most interesting information on the cultural heritage of Kazakhstan is available in the collection of documents and photographs like V.I. Mezhova’s «Collection of Turkestan», A.L. Kuhn’s «Album Turkestan» Archive Office of the Turkestan Governor-General; as well as a collection of «Turkestan region» of A.G. Serebrennikov. The collection of Turkestan is the written source of the cultural heritage of Central Asian Turks in the 19th century. Leafing through the pages of the collection the volume after volume, we can restore the entire life of the region in detail on the state of socio-economic development, the study of the productive forces, the rich resources to the study of the historical past, life, traditions, customs and character of the people who inhabited the region, the theatre of military events, conquests and liberation wars, as well as get acquainted with the research works.
Keywords: cultural heritage; written sources; Central Asian Turks; library collection; Turkestan collection; Central Asian